Nonsymmetric Myocardial Contribution to Supranormal Right Ventricular Function in the Athlete's Heart: Combined Assessment by Speckle Tracking and Real Time Three‐Dimensional Echocardiography. Issue 8 (24th December 2013) - Esposito, Roberta; Galderisi, Maurizio; Schiano‐Lomoriello, Vincenzo; Santoro, Alessandro; De Palma, Daniela; Ippolito, Renato; Muscariello, Riccardo; Santoro, Ciro; Guerra, Germano; Cameli, Matteo; Mondillo, Sergio; De Simone, Giovanni
<x xml:space="preserve">Abstract</x> Purpose To investigate determinants of right ventricular (RV) function in competitive athletes by a combined assessment of speckle tracking (STE) and real time 3D echocardiography (RT3DE). Methods Right ventricular function of 40 top‐level rowers was compared to 43 sedentary normal controls by standard Doppler echocardiography, RT3DE, and STE. RV diameters and wall thickness, tricuspid annular plane systolic excursion (TAPSE), tricuspid E/A ratio, and pulsed tissue Doppler of lateral tricuspid annulus were analyzed. RV volumes, ejection fraction (EF), and stroke volume (SV) were determined. RV global longitudinal strain (GLS) (average of 6 regions), septal strain (average of 3 septal regions, septal longitudinal strain [SLS]), and lateral strain (average of 3 lateral regions, lateral longitudinal strain [LLS]) were estimated by STE. Results The 2 groups were comparable for age, body mass index, and blood pressure, but heart rate was lower in rowers. RV diameters were larger and TAPSE, tricuspid E/A ratio, and tissue Doppler‐derived s′ and e′ velocities were higher in rowers. By RT3DE, RV end‐diastolic volume (EDV) and end‐systolic volume were greater in rowers (both P < 0.0001), without difference in EF. GLS (P < 0.005) and LLS (P < 0.001), but not SLS, were greater in rowers. In pooled groups, LLS was related to EDV and SV, even after adjusting for heart rate, body mass index, and RV wall thickness by separate multiple linear regression analyses (β coefficient = 0.247, P < 0.01 and β = 0.225, P < 0.02, respectively). Conclusions Right ventricular preload exerts its maximal influence on the longitudinal lateral fibers, which is independent on potential confounders and largely induces RV supranormal function in the athlete's heart.